ANALISIS HUBUNGAN PENDAPATAN ASLI DAERAH,DANA ALOKASI UMUM, DANA ALOKASI KHUSUS, DANA BAGI HASIL, DAN SISA LEBIH PEMBIAYAAN ANGGARAN TERHADAP BELANJA MODAL DI KABUPATEN ACEH TENGGARA PERIODE TAHUN 2008-2017 - Ernita Odilia Siburian; Hijri Juliansyah (Jurnal Ekonomi Regional Unimal, 2019)
This study aims to analyze the interrelation of Regional Own Revenue, General allocation fund, Specific Allocation Fund, Revenue Sharing Fund, and Financing Surplus toward Capital Expenditure Budget in Southheast Aceh’s regency. The data that used in this research was from secondary data of 2008-2017 year. Data was collected from BPKD southeast Aceh. The model of research analysis used Multivariate Vector Autoregression (VAR) with Impluse Reseponse Function (IRF) and Forecast Error Varian Decomposition (FEVD). The result of this research used the model of Multivariate Vector Autoregression’s analysis which showed that there was no interrelation (causality) between Regional Own Revenue toward Capital Expenditure and both of them were influenced each other.. The result of this research showed that there was contribution in each variable to its variable and others variable.